2021
DOI: 10.1212/wnl.0000000000011699
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Profile and Markers of Alzheimer Disease–Type Pathology in Patients With Lewy Body Dementias

Abstract: ObjectiveTo determine whether patients with Lewy body dementia (LBD) with likely Alzheimer disease (AD)–type copathology are more impaired on confrontation naming than those without likely AD-type copathology.MethodsWe selected 57 patients with LBD (dementia with Lewy bodies [DLB], n = 38; Parkinson disease dementia [PDD], n = 19) with available AD CSF biomarkers and neuropsychological data. CSF β-amyloid1-42 (Aβ42), phosphorylated-tau (p-tau), and total-tau (t-tau) concentrations were measured. We used an aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 56 publications
1
29
0
Order By: Relevance
“…Although most evidence has indicated an α-syn pathology in the development of PDD, there is a notable heterogeneity in symptomatology and timing of dementia between PDD cases. An increasing number of studies have shown that LBs, AD-type pathology, and iron dysmetabolism appear to contribute to the emergence of PDD (Smith et al, 2019 ; Kouli et al, 2020 ; Howard et al, 2021 ). It is possible that α-syn is transmitted from degenerating neurons into neighboring neurons and non-neuronal cells; indeed, α-syn aggregates have been found in the SN, the nucleus basalis of Meynert, cerebral cortex, locus coeruleus, cranial nerve motor nuclei, and locus coeruleus (Braak et al, 2006 ; Brundin and Melki, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most evidence has indicated an α-syn pathology in the development of PDD, there is a notable heterogeneity in symptomatology and timing of dementia between PDD cases. An increasing number of studies have shown that LBs, AD-type pathology, and iron dysmetabolism appear to contribute to the emergence of PDD (Smith et al, 2019 ; Kouli et al, 2020 ; Howard et al, 2021 ). It is possible that α-syn is transmitted from degenerating neurons into neighboring neurons and non-neuronal cells; indeed, α-syn aggregates have been found in the SN, the nucleus basalis of Meynert, cerebral cortex, locus coeruleus, cranial nerve motor nuclei, and locus coeruleus (Braak et al, 2006 ; Brundin and Melki, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of LBs and AD-type pathology is considered to have a strong pathological association with PDD (Irwin et al, 2013 ). Clinical studies have shown that PDD is associated with severe α-syn pathology in the hippocampus and entorhinal and occipitotemporal cortexes, and Aβ pathology and tau pathology in the striatum (Smith et al, 2019 ; Kouli et al, 2020 ; Howard et al, 2021 ). The combination of LBs, Aβ, and tau pathologies has a strong correlation with the pathology in patients with PDD (Compta et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…That is, PD patients with aSyn pathology found not only in the brainstem but also throughout the limbic system and cortex are more likely to have cognitive impairment than PD patients with less extensive aSyn pathology [ 46 ]. People with PD and concomitant AD have more severe motor dysfunction, a higher burden of depression, faster rate of cognitive progression, shorter interval from motor to cognitive symptom onset, impaired language performance, higher rate of nursing home admittance, and higher mortality risk, compared to PD patients without AD pathology [ 46 , 47 , 48 ]. Specifically, temporal lobe tau burden has been independently associated with antemortem deficits in confrontation naming [ 40 , 49 ].…”
Section: Ad Pathology Is Common In Pd Brains and Is Associated With Worse Cognitive Performance During Lifementioning
confidence: 99%
“…Evidence suggests that these Alzheimer markers likely reflect concomitant Alzheimer pathological process along with the Lewy body disease. Specifically, AD biomarkers in DLB (DLB-AD) are associated with increased age, female sex, increased APOE ε4 genotype, decreased memory, increased delusions and hallucinations, less REM-behavior sleep disorder and parkinsonism, worse language performance, faster progression, increased temporal thinning and tau pathology, and greater risk of institutionalization and mortality (2)(3)(4)(24)(25)(26)(27)(28). These findings are corroborated by post-mortem clinicopathologic studies showing that AD pathologic features (neuritic plaques and also tangles) in cases clinically defined as "probable DLB" are associated with an atypical "Alzheimerized" clinical presentation (e.g.…”
Section: Biomarkers For Alzheimer's Disease Pathologymentioning
confidence: 99%